VAT collection efficiency in Poland before and after accession to the European Union–a comparative analysis - Hybka, Małgorzata Magdalena (Ekonomika, 2009)
The principal aim of this study is to evaluate the impact of EU accession on VAT collection efficiency in Poland. For the purposes of the analysis the article is divided into three parts. The first addresses the Polish economy in the years 2001–2006, and describes the main macroeconomic indicators (GDP, import, export, individual consumption expenditure, public consumption expenditure, inflation rate and unemployment rate). The next section presents a review on the most significant VAT modifications, implemented in 2004. The last section estimates, on the basis of certain indicators, the VAT collection efficiency in the years 2001–2006. The measures employed in this section include: VAT productivity and VAT efficiency ratio. Furthermore, the section presents the VAT to GDP ratio and the structure of tax receipts measured by the share of major taxes in the total tax collection. The main conclusion drawn from the analysis is that in the period preceding accession the economic cycle did not favuor VAT performance. Since 2004, both improved economic situation and tax construction changes had been the main factors of VAT revenue increase. In the years following accession the VAT productivity and VAT efficiency ratios increased by 5,4 and 7,8 percentage points, respectively. It was the highest rise of these indicators in the period analyzed.